2021
DOI: 10.1016/j.chemosphere.2020.127784
|View full text |Cite
|
Sign up to set email alerts
|

Nanoplastic occurrence in a soil amended with plastic debris

Abstract: While several studies have investigated the potential impact of nanoplastics, proof of their occurrence in our global environment has not yet been demonstrated. In the present work, by developing an innovative analytical strategy, the presence of nanoplastics in soil was identified for the first time. Our results demonstrate the presence of nanoplastics with a size ranging from 20 to 150 nm and covering three of the most common plastic families: polyethylene, polystyrene and polyvinyl chloride. Given the amoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
103
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 238 publications
(122 citation statements)
references
References 37 publications
2
103
0
2
Order By: Relevance
“…It is likely that effects will shift to direct chemical toxicity, compared to the more indirect effects of MP, as already shown for plants [43]. Analytical methods for NP are currently under development, and it appears that NP particles are indeed present in the soil matrix [44]. Consequences of NP for soils are unclear since there are only very few studies [45,46], and thus it is presently not understood how they would influence ecosystem processes, such as soil C processing and storage.…”
Section: Nanoplasticsmentioning
confidence: 89%
“…It is likely that effects will shift to direct chemical toxicity, compared to the more indirect effects of MP, as already shown for plants [43]. Analytical methods for NP are currently under development, and it appears that NP particles are indeed present in the soil matrix [44]. Consequences of NP for soils are unclear since there are only very few studies [45,46], and thus it is presently not understood how they would influence ecosystem processes, such as soil C processing and storage.…”
Section: Nanoplasticsmentioning
confidence: 89%
“…On the other hand, nanoplastics (NPs) are polymer particles within the size range from 1 to 1000 nm that are unintentionally produced as a result of the degradation of microplastics, and are capable of exhibiting a colloidal behavior (Gigault et al, 2017, Gigault et al, 2018Wagner and Reemtsma, 2019;Wahl et al, 2021). While degradation of aged-plastic or the fragmentation particles of especially macro-and/or microplastics is the principal mechanism of nanoplastics formation in the terrestrial and marine environments, NPs could be released from intentional channels such as manufacturing process, washing fibrous materials, plastic object usage (Bouwmeester et al, 2015;Gilgault et al, 2018;Hartmann et al, 2019;El Hadri et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…According to Gilgault et al (2018) andEl Hadri et al (2020), NPs are mono-and polydispersed mix of several polymeric substances that are capable of undergoing heteroaggregation with various natural and man-made species including metal (loids), organic molecules and metal oxides during the process of formation and transformation in the environment. Although there are very limited studies on the sorption potentials and the sparse information associating chemical additives and organic pollutants with NPs, a recent study has suggested that the relatively smaller size, morphology, enhanced surface reactivity and diffusion properties could influence the sorption behavior of NPs (El Hadri et al, 2020;Wahl et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…However, plastic debris size reduction proceeds beyond the microscale [8][9][10]. Plastic particles at the nanoscale, called nanoplastics (NPs) [11], have been recently detected in samples from the open ocean [12] to soil [13]. The definition of NPs is still under debate; for instance, for more than a decade, there has been no consensus on their upper size limit, which ranges from 1 µm down to 100 nm [14][15].…”
Section: Introductionmentioning
confidence: 99%